Un nuevo dispositivo de bajo costo y fácil acceso para el tratamiento de las fracturas deprimidas en “ping pong” de forma no quirúrgica. Nota técnica. - Minghinelli, Federico Eduardo; Bourguet , Martín; Biancardi , Mauro; Badilla , Tomás; Houssay, Alfredo (Revista Argentina de Neurocirugía, 2024)
Objective: The aim of this paper is to describe a low-cost and readily accessed Manual Aspiration Reduction System (MARS) for use treating ping-pong fractures in three patients. Method: The MARS is composed of a pediatric anesthesia mask, part of a macro dripper, a 3-way stopcock, and two 60-ml syringes. Prior to its use in our patient, the system was tested on five adult volunteers to maximum negative pressure, and none reported pain during the procedure or experienced any other complication. We present five clinical cases of patients with depressed ping-pong fracture who were treated with the MARS at the bedside without anesthesia. The patients were monitored by the neonatology team throughout the procedure. Results: Skull radiography revealed reduction of the fracture after the procedure performed with the MARS in all patients. The transfontanellar ultrasound and follow-up neurological examination were normal. The patient progressed favorably and was discharged from our service after 24 h. Conclusions: Due to its components, the MARS is a low-cost and readily accessed system. In this case, it permitted satisfactory reduction of a ping-pong fracture in all patients. This system should greatly simplify the treatment of such fractures.